Nurses' authority in Neonatal Intensive Care Units (NICUs) in Israel- The disparity between policy and Practice - Orly Toren; Yehuda Tsur; Nurit Nirel; Assaf Toker; Michal Lipschuetz (Archives of Nursing Practice and Care - Peertechz Publications, 2019)
Background: Policy implementation is a fundamental aspect in management. This study examined gaps and barriers in the implementation process of governmental policy with respect to the division of responsibility and authority between physicians and nurses. In this study we aimed to examine the work processes and actual division of labor between physicians and nurses in the Neonatal Intensive Care Units (NICUs) and the disparities between them and the Israeli Ministry of Health policy (MOH) and to examine the attitudes of staff members towards the need for policy change Methods: A cross-sectional study, conducted among physicians and nurses at 22 NICUs in Israel. 432 recruited (50% rate). Results: A disparity was found between policy and actual practice. Many of the tasks permitted to RNs by law or regulations are not actually performed by them.